Attitudes toward oocyte donation among medical and nursing students and couples who have recently become parents: A Swedish study - SYDSJÖ, GUNILLA (Reprod Med Biol, 2008)
Aim:  The aim of the present study was to investigate attitudes toward oocyte donation and receiving oocytes in relation to gender, demographic variables and other factors that could influence these attitudes, such as anonymity of the donor and financial compensation. Methods:  The study population consisted of 595 subjects divided into two groups; one group contained men and women who had recently become parents and the other group consisted of medical and nursing students. All subjects were asked to answer a study‐specific questionnaire. Results:  The proportions of respondents positive toward oocyte donation were 32% in the student group and 37% in the parental group. Of the respondents in the student group, 87% were positive toward donating organs other than oocytes compared with 78% in the parental group (P < 0.05). In the parental group, the respondents that were positive toward organ donation in general were also more positive toward donating/partner donating and receiving/partner receiving oocytes (P < 0.001 and P < 0.01, respectively). The majority of the respondents stated that their attitudes were not affected by anonymity of the donation, financial compensation or knowing the outcome of the donation. Conclusion:  Respondents’ attitudes were unaffected by anonymity of the donation, financial compensation and knowing the outcome of the donation. However, the data suggest that respondents who were positive toward organ donation in general were also more positive toward donating/partner donating and receiving/partner receiving oocytes. (Reprod Med Biol 2008; 7: 161–168)